Effect of Nitrogen Levels on Growth and Yield of Maize - Odunayo, Okanlawon Elizabeth (Journal of Posthumanism, 2026)
Nitrogen is a critical nutrient influencing crop growth, productivity, and food security in cereal-based farming systems. Maize (Zea mays L.), a staple crop in many developing countries, exhibits strong responses to nitrogen fertilisation due to its high nutrient demand. However, inappropriate nitrogen management, either insufficient or excessive application, can reduce yield efficiency and increase environmental risks. This study evaluated the effects of varying nitrogen levels on maize growth and yield under field conditions. Five nitrogen treatments (0, 60, 120, 180, and 240 kg N ha⁻¹) were arranged in a randomised complete block design with three replications. Vegetative growth parameters, including plant height, number of leaves, leaf area, and biomass, were measured alongside yield components, including cob length, grains per cob, thousand-grain weight, and grain yield. Results showed that nitrogen fertilisation significantly improved both vegetative growth and yield components compared to the control treatment. Optimal performance was observed at 180 kg N ha⁻¹, which produced the highest grain yield (5000 kg ha⁻¹). Increasing nitrogen beyond this level produced only marginal yield gains, indicating diminishing returns. The findings highlight the importance of balanced nitrogen management to maximise maize productivity while minimising economic and environmental costs. These results provide practical guidance for sustainable fertiliser management in maize production systems.